2012
DOI: 10.1016/j.ijgo.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of early transverse annular compression sutures for complete placenta previa during cesarean delivery

Abstract: Early implementation of TACS could lead to improved maternal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Early in 2012, our team found that the transfusion rate could be greatly reduced if transverse annular compression sutures were applied when the bleeding volume reaches 500 mL. Early intervention can reduce both blood loss and the volume of blood transfused . In 2011, Kayem and colleagues found that a prolonged delay of 2 to 6 hours between delivery and uterine suture placement was significantly associated with an increased risk of hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early in 2012, our team found that the transfusion rate could be greatly reduced if transverse annular compression sutures were applied when the bleeding volume reaches 500 mL. Early intervention can reduce both blood loss and the volume of blood transfused . In 2011, Kayem and colleagues found that a prolonged delay of 2 to 6 hours between delivery and uterine suture placement was significantly associated with an increased risk of hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Early intervention can reduce both blood loss and the volume of blood transfused. 35 In 2011, Kayem and colleagues 36 found that a prolonged delay of 2 to 6 hours between delivery and uterine suture placement was significantly associated with an increased risk of hysterectomy. Based on the findings of our present study, we put forward a hypothesis that earlier application of conservative surgery for PPH, such as uterine compression sutures, intrauterine balloon compression therapy, or uterine artery ligation, may significantly reduce the volume of obstetric blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Lu suture does seem to effectively stop bleeding within the lower uterine segment. Folding sutures specialized for lower uterine segment bleeding are reported to be extremely efficient [12–16]. For example, in one study [13], the success rates of uterine packing alone or transverse annular compression sutures alone were 91.7% and 94.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of such sutures has markedly decreased maternal mortality associated with PPH, these methods cannot always stop bleeding within the lower uterine segment. Therefore, various specialized folding sutures were developed to control bleeding in this anatomical region, such as circular isthmic–cervical compression sutures [12], transverse annular compression sutures [13,14], parallel vertical compression sutures [15], and double vertical compression sutures [16]. These folding sutures resolve most cases of lower segment PPH.…”
Section: Introductionmentioning
confidence: 99%
“…First‐line treatments of PPH include the manual removal of retained placental tissue, uterine massage, application of bimanual compression, continuous intravenous application of oxytocin, and volume replacement. If first‐line therapies are not successful, second‐line treatment of PPH must be undertaken, such as sulprostone infusion, compression sutures [2,3], uterine sandwich (B‐lynch suture and balloon tamponade), selective arterial embolization [4,5], or hysterectomy. The appropriate second‐line procedure may achieve hemostasis of intractable hemorrhage and prevent the need for more severe surgical procedures.…”
Section: Introductionmentioning
confidence: 99%